Entrepreneurship theory, process, practice - Kuratko, Donald F. (Cengage, 2024)
Learn about the entrepreneurial mindset and the true process of a successful entrepreneur with Kuratko's Entrepreneurship: theory, process, practice, 12th edition! Presenting the most current thinking in this explosive field, this renowned entrepreneurship text provides a practical, step-by-step approach that makes learning easy.